Management of vascular Behcet's disease - (:unkn) unknown (WILEY, 2019)
y Behcet's disease (BD) is a chronic, multisystemic, inflammatory disease characterized by recurrent attacks of mucocutaneous, ocular, musculoskeletal, vascular, central nervous system and gastrointestinal manifestations. Treatment of BD changes according to organ involvement, gender and age of the patient with no golden standard therapeutic regimen. Vascular involvement is observed in up to 40% of the patients with BD, especially in young males and is one of the major causes of mortality and morbidity. Glucocorticoids, azathioprine and cyclophosphamide are still recommended as the first-line treatments in vascular BD. However, increasing data with the tumor necrosis factor inhibitors suggest that these agents may also be acceptable options for the management of refractory vascular BD in daily practice. Anticoagulant usage for vascular BD is also still controversial with limited data coming from retrospective studies. There is a clear need for randomized, controlled studies for the management of VBD.
Keywords: Behcet's disease; TNF inhibitors; vascular involvement